Internet of Things in Education: A Brief Overview - Sadiku, Matthew N. O.; Chukwu, Uwakwe C.; Sadiku, Janet O. (Researchparks Publishing, 2023)
The Internet of things (IoT) is essentially the connection of devices to the Internet. IoT network connects various types of devices like tablets, smartphones, personal computers, laptops, and wearable devices. The education sector is deploying IoT devices in order to make education more collaborative, interactive, and accessible to all. IoT devices are changing the way we process and absorb information for the better. IoT application has the potential to provide a better-connected and more collaborative way for educators to engage with students. Today, IoT is preferred as a means of learning, teaching, and research in education. This paper presents a short overview on the uses of the Internet of Things in education, highlighting potentialities and challenges.